2015
DOI: 10.1016/j.ebiom.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Muscle A-Kinase Anchoring Protein-α is an Injury-Specific Signaling Scaffold Required for Neurotrophic- and Cyclic Adenosine Monophosphate-Mediated Survival

Abstract: Neurotrophic factor and cAMP-dependent signaling promote the survival and neurite outgrowth of retinal ganglion cells (RGCs) after injury. However, the mechanisms conferring neuroprotection and neuroregeneration downstream to these signals are unclear. We now reveal that the scaffold protein muscle A-kinase anchoring protein-α (mAKAPα) is required for the survival and axon growth of cultured primary RGCs. Although genetic deletion of mAKAPα early in prenatal RGC development did not affect RGC survival into adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 43 publications
(70 reference statements)
6
29
0
Order By: Relevance
“…Confocal images were acquired with a confocal laser scanning microscope (Zeiss 880) and a ϫ10 magnification lens. The imaging and quantification were performed in a masked fashion as previously described (Wang et al, 2015). Briefly, the retinas were divided into four quadrants, and one digital micrograph was taken from a fixed distance from the periphery of each of the four fields.…”
Section: Cell Culturementioning
confidence: 99%
See 4 more Smart Citations
“…Confocal images were acquired with a confocal laser scanning microscope (Zeiss 880) and a ϫ10 magnification lens. The imaging and quantification were performed in a masked fashion as previously described (Wang et al, 2015). Briefly, the retinas were divided into four quadrants, and one digital micrograph was taken from a fixed distance from the periphery of each of the four fields.…”
Section: Cell Culturementioning
confidence: 99%
“…We have demonstrated that mAKAP␣ expression is required for neurite growth in vitro and neuronal survival in vivo (Wang et al, 2015), but how its perinuclear localization affects these processes has not been explored. mAKAP is localized to the nuclear envelope via protein-protein interactions with KASH domain-containing, transmembrane isoforms of nesprin-1 that heterodimerize via their spectrin-repeat domains with mAKAP (Pare et al, 2005a).…”
Section: Makap␣ Anchoring By Nesprin-1␣ Is Required For Neurite Extenmentioning
confidence: 99%
See 3 more Smart Citations